KARAKTERISTIK RUSIP IKAN RUCAH DENGAN PENAMBAHAN KONSENTRASI GULA AREN CAIR DAN GARAM BERBEDA - Koesoemawardani, Dyah -; Endi Hermawan, Yogi; Herdiana, Novita; Susilawati, Susilawati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
Trash fish is a fish with low selling value that needs an increased value by processing it into rusip (fermented fish) products. The research objective was to determine the effect of liquid palm sugar and salt concentrations on the physical, chemical, and microbiological properties of trash fish rusip. The research was arranged factorial in a completely randomized block design. The concentrations of liquid palm sugar were 5%, 10%, and 15% (v/w), while concentrations of salt were 20%, 25%, and 30% (w/w).Â Using LSD at level 5% showed that the concentration of liquid palm sugar had a significant effect on total lactic acid bacteria and total lactic acid, while the salt concentration had a significant effect on pH and salt content. There was an interaction between two factors on the trash fish rusip water content, where the significant effect of liquid palm sugar concentration on water content was salt concentration-dependent.Keywords: chemical, microbiological, physical, rusip, trash fish.